I.M. Sechenov: professional and personal qualities of scientist (to the 185-th anniversary of the prominent russian physiologist) - L. A. Pomelova; I. I. Shevelev; N. E. Vazheevskaya; R. V. Shurupova (Сеченовский вестник)
The article under review presents a brief biography of life and work of I.M.Sechenov, shows common destiny of many scientists — his contemporaries. The contribution of I.M.Sechenov in the world medical science and education is analyzed. It is noted that the fate of scientists, as well as of ordinary people, are very different. This was an outstanding Russian physiologist, psychologist, pathologist, histologist, toxicologist, cultural anthropologist, chemist, physicist, biochemist, evolutionist, military engineer, teacher, writer, humanist, philosopher and rationalist, creator of the physiological school; Honored ordinary professor, corresponding member of the Biological category (1869–1904), an honorary member (1904) of the Imperial Academy of Sciences;holder of the Orders of St. Stanislaus I degree, of St. Anne III degree, of St. Vladimir III degree.